Upaya Menjaga Raja Ampat sebagai Sustainable Tourism Melalui Prinsip Sustainabilty dan Blue Economy - Nailah Nur Azizah; Nurjannah Abdullah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This journal addresses efforts to maintain Raja Ampat as Sustainable Tourism through Sustainability and Blue Economy Principles. Raja Ampat is one of the tourism destinations in Indonesia that needs to maintain its tourism attractiveness while maintaining the surrounding nature. This research presents strategic steps that can be taken to encourage sustainable tourism. The research methodology was conducted through library research, which resulted in the conclusion that to maintain Raja Ampat as sustainable tourism requires the active involvement of local communities, stakeholders and the role of the government. The implementation of this sustainable improvement strategy can be in the form of tourism promotion, infrastructure development and empowerment of local communities.